The Use of Dictogloss in Teaching Listening Comprehension for EFL Learners - Asrobi, Maman; Amni, Khaerul (VELES Voices of English Language Education Society, 2017)
The objective of this study was to know the effectiveness of dictogloss in teaching listening comprehension. The design of this research was a pre-experimental research design. To collect the data, a pre-test and a post-test was given to the tenth graders of MA Muallimat NW Pancor (30 students). In order to examine the effectiveness of dictogloss, the collected data were submitted to a paired samples t-test by using SPSS 17 for windows. Based on the result of study, the mean score of pre-test (11.10) was lower than post test (13.57). After submitting the data to a paired samples t-test, the present researcher found that there was a significant difference in the mean scores between the pre-test and the post-test, t(df=29) = 16.49 at p  ˂ .01, meaning that the null hypothesis was rejected and alternative hypothesis was accepted. Dictogloss was significantly effective in teaching listening comprehension for the tenth graders of MA Muallimat NW Pancor in the school year 2015-2016. Considering the process and the results of this research, the present researcher suggested that the English teacher use dictogloss as the technique to teach the students.